Inquéritos populacionais referentes à epidemiologia das violências no cenário rural: revisão de escopo - Bandeira, Carmem Layana Jadischke (2023)
This review had the overall goal of mapping population-based surveys related to the epidemiology of violence in rural settings and demographic characterization variables. It is a Scoping Review conducted using the JBI methodology. The research question was: "What are the population-based surveys that address violence against people residing in rural settings and demographic characterization variables?" developed by the mnemonic "PCC," which stands for Population, Concept and Context. Included in the study were individuals experiencing violence, population surveys, and rural contexts. Excluded were studies that analyzed the consequences of violence, did not relate to rural areas, or did not pertain to private households. A three-stage search strategy was developed, searching for studies in ten databases. The selection of evidence sources was carried out independently by two reviewers, with conflicts resolved by a third reviewer. A narrative description of the selection process was presented in the PRISMA-ScR flowchart. The Rayyan® software was used for managing the results, and data extraction was performed using a form. The evidence analysis was descriptive, and the data were presented in diagrammatic, tabular, and descriptive forms. Most of the located studies had a crosssectional design, with no description of the sample definition technique and data collection instruments. For data collection, the majority used household questionnaires, the predominant age group was adults, and the majority of the studies focused on the female gender. The highest number of studies was in the Asian continent, the number of publications increased during the pandemic, and the majority of victims during this period were women. For data analysis, descriptive and inferential statistical analysis and the SPSS program predominated. The most common types of violence were psychological violence (39.81%), physical violence (29.13%), sexual violence (14.57%), neglect (4.85%), controlling behavior (1.94%), bullying (1.94%), violence without typology (1.94%), physical and sexual violence (1.94%), physical and psychological violence (0.97%), domestic violence (0.97%), intimate partner violence (0.97%), and violence without a description of the type (0.97%). Most studies did not describe the locations where the cases of violence occurred and whether they took place in private households. The main perpetrators were intimate partners and husbands. Thus, the rural setting is recognized as a space of care with its unique characteristics, where geopolitical, social, cultural, epidemiological, and organizational factors are specific. The aim was to shed light on the issue of violence in this context, particularly.